2017
DOI: 10.1159/000481920
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Surprise Question Compared to Prediction Models in Hemodialysis Patients: A Prospective Study

Abstract: Background: The surprise question (SQ) (“Would you be surprised if this patient were still alive in 6 or 12 months?”) is used as a mortality prognostication tool in hemodialysis (HD) patients. We compared the performance of the SQ with that of prediction models (PMs) for 6- and 12-month mortality prediction. Methods: Demographic, clinical, laboratory, and dialysis treatment indicators were used to model 6- and 12-month mortality probability in a HD patients training cohort (n = 6,633) using generalized linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The Surprise Question has been validated in patients with cancer and in those with and without dialysis‐dependent chronic kidney disease in whom it reliably and accurately predicts survival . Although decompensation of heart failure requiring hospitalisation is a poor prognostic sign, many patients subsequently have long periods of relative stability, and it is this characteristic non‐linear trajectory of heart failure which casts doubt as to whether the Surprise Question is an appropriate tool.…”
Section: Introductionmentioning
confidence: 99%
“…The Surprise Question has been validated in patients with cancer and in those with and without dialysis‐dependent chronic kidney disease in whom it reliably and accurately predicts survival . Although decompensation of heart failure requiring hospitalisation is a poor prognostic sign, many patients subsequently have long periods of relative stability, and it is this characteristic non‐linear trajectory of heart failure which casts doubt as to whether the Surprise Question is an appropriate tool.…”
Section: Introductionmentioning
confidence: 99%
“…The discrimination in our study (area under the curve: 0.62) is generally weaker than in other studies. 12 , 20 , 35 , 36 However, a previous study also found lower discriminatory values for endpoints other than mortality. 30 Another study about the Surprise Question conducted at the emergency department measured acute morbidity as the endpoint and also resulted in a lower area under the curve for nurses (0.68) and patients (0.54), similar to our results.…”
Section: Discussionmentioning
confidence: 83%
“…Our study also included a survival rate of fewer than 6 months estimated by the doctor treating the patient. In spite of the fact that it is a subjective variable, its usefulness as a screening tool to identify patients at the end of life has been proven in cancer 28 and chronic kidney disease 29 . Recent studies 30,31 have also shown the validity of the Surprise Question (‘Would you be surprised if your patient died within 1 year?’) in predicting mortality in HF.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that it is a subjective variable, its usefulness as a screening tool to identify patients at the end of life has been proven in cancer 28 and chronic kidney disease. 29 Recent studies 30 , 31 have also shown the validity of the Surprise Question (‘Would you be surprised if your patient died within 1 year?’) in predicting mortality in HF. Surprisingly, the intuitive prediction of physicians in our score turned out to be the strongest predictor along with the age over 85 years.…”
Section: Discussionmentioning
confidence: 99%